Multi-agent collision approach for stabilizing multi-machine power networks with distributed excitation systems. (30th September 2018) - Wang, Cui; Zhou, Jun; Duan, Zhaoxia
Abstract: Stabilization in terms of frequency synchronism and power angle specification in multi-machine power networks is addressed by distributed multi-agent flocking control actuated through excitation systems (ES), while taking into account static var compensators (SVC) as auxiliary control for other generator performances. More precisely, frequency synchronism and power angle specification in a multi-machine power system are re-formulated as formation control of multiple generator agents in the corresponding multi-agent network. By inducing multi-agent collision under virtual controls defined by the generalized Olfati-Saber's flocking algorithm, stabilization among all synchronous generators is achieved while the steady-state torque angles are specified to a same power angle. Distributed real control actions of ES's are determined via nonlinear algebraic and differential equations for individual generators with respect to the virtual controls. Numeric examples of a three-machine power network are included to illustrate the main results.